B2.3 Improving feedback for hospitals referring children to the children's acute transfer service. (4th October 2017) - Manning, GLP; Chigaru, L
Abstract : Background: Hospitals referring children to the Children's Acute Transfer Service (CATS) regularly ask for more and better-quality feedback. Mechanisms exist for feedback following critical incidents, but no stabilisation- and transfer-specific feedback is given for routine cases. As part of a project to improve feedback to referring hospitals, a CATS discharge letter was planned: the transporting fellow would enter feedback into the CATS database, which after consultant moderation, would be included into a transfer discharge letter. This report relates to improving feedback generation. Methods: For the primary driver of feedback documentation, secondary drivers of consideration, documentation on paper, and transcription into the CATS database were identified. For the primary driver of feedback quality, secondary drivers of multidisciplinary input and retrospective team discussion were identified. An A3 project proposal document was created after team discussion. Progress was measured by graphing percentage of cases with paper feedback, and cases with correct database entry. Change ideas included regular feedback on progress; explanatory posters; inclusion on the safety brief; review of feedback in morning meeting case discussions; targeted verbal and email feedback; review of database field labelling; reviewing timing of database entry; and feedback from moderating consultants. Results: Over the first 7 weeks, feedback completion rates improved from 30% to 83%, with consistent week-on-week improvements. Correct database entry was variable, ranging from 20%–92% of cases with feedback, with significant week-to-week variability. Discussion: Widespread CATS team support and a high profile, along with up-to-date progress monitoring and a range of targeted interventions have helped ensure that feedback is collected for most cases. Database entry has been variable, with inconsistent and absent data entry, and is an area for ongoing intervention. Conclusion: After seven weeks, referral feedback is being collected frequently enough to implement CATS discharge letters. Future PDSA cycles will review database entry and feedback quality.